Analisis Asam Lemak Omega 3 dan 6 pada Minyak Ikan Lele secara GC-FID - Pandiangan, Maruba; Kaban, Jamaran; Wirjosentono, Basuki; Silalahi, Jansen (Universitas Katolik Santo Thomas Medan, 2020)
Omega 3 and 6 fatty acids are very good consumed to improve human health. For this reason, research is needed to determine the glyceride profile and identification of omega 3 and 6 fatty acids in fat molecules so that the potential of catfish oil as a source of omega 3 and 6 can be known. Catfish oil was extracted by the soxletation method. Fatty acid composition was analyzed by gas chromatography (GC-FID) which was previously esterified using BF3. The results showed that the composition of unsaturated fatty acids more than saturated fatty acids. Omega-3 fatty acids are found consisting of linolenic acid, eicosapentanoic acid (EPA) and docosahexanoic acid (DHA) and omega 6, namely linoleic acid. The comparison of omega 3 and omega 6 in catfish oil is still within the recommended comparison terms. Judging from the composition and position of catfish oil fatty acids which contain omega 3 and omega 6 fatty acids. Thus catfish oil has the potential as a source of omega 3 and 6 from one of the freshwater fish that are consumed by many people.